Importancia del enfunde en el control de insectos y calidad de racimo de banano (Musa spp.) - Muñoz Noboa, Janeth Michelle (2022)
Abstract The objective of this research was to determine the importance of the casing in the control of insects and bunch quality in banana cultivation. For this, a bibliographical exploration was carried out, of different sources of scientific information that have highlighted the applicability and benefits of the wrapping of banana bunches. The sleeve offers great benefits to the producer since it protects the bunch, with a perforated polyethylene sleeve of the appropriate dimensions, from the damage caused by insects, leaves, chemical products, achieving a cleaner and excellent quality fruit. Among the different casing variants, there are Chemplast, Tharza and Plastivill, of which the first two have four variants, highlighting Plastivill (Pv-Pyrcoban alone), which presented greater efficacy for the control of the dump worm (Pyroderces rileyi), mealybugs (Dysmicoccus texensis) and aphids (Pentalonia nigronervosa), while for Thrips (Frankiniella parvula), the most efficient is Chemplast (B + 3 Ties N.F IS), reflecting that on average Plastivill (Pv- Pyrcoban alone) is the most efficient alternative. efficient. Finally, it was possible to identify that among the benefits of casing in banana cultivation, it has become essential to increase yield and improve fruit quality, in addition, a microclimate is created that maintains a high temperature around of the cluster and prevents it from being damaged by cold, as well as it can reduce the interval from flowering to harvest by many days.